Design and Calculation of the New Distribution Network Branch - Frechová, L. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
The aim of the project is to provide a summary about design and calculation of the new distribution network branch. It solves the problem of the selection of a suitable transformer and conductor and it shows results of application of base calculation methods.
Keywords: Distribution network; transformer station; cable line